Eicosanoid and cytokine levels in plasma of patients during mesenteric infarction - N. Nathan; Y. Denizot; P. Feiss (Mediators of Inflammation)
Multible organ failure (MOF) induced by mesenteric infarction is associated with a high mortality rate. This study reports eicosanoid and cytokine levels in the blood of three atherosclerotic patients who ultimately died from MOF induced by mesenteric infarction. High plasma levels of 6- keto-prostaglandin (PG) F1α (the stable metabolite of PGI2), interleukin (IL)-6 and IL-8 are observed whereas plasma tumour necrosis factor alpha (TNFα), TxB2 (the stable metabolite of TxA2), PGE2, leukotrienes (LT)B4 and LTC4, and whole blood platelet-activating factor levels are not different from values obtained in similarly severe atherosclerotic patients. This short report questioned the clinical involvement of TNFα during such a pathology where a persistent translocation of endotoxin has been observed through the gut endothelial barrier. Activation of phospholipase A2 is suggested by the increase in the stable metabolite of PGI2 and might be by itself or through lipidic metabolites, a major systemic stimulus of IL-6 and IL-8 production.